PENGARUH MEDIA ONLINE TRIBUN AMBON TERHADAP INFORMASI CEPAT KEPADA PUBLIK - Amelia Tahitu; Demsy Wattimena (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
Quantitative research can be interpreted as a method based on the philosophy of positivism, used to research certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical with the aim of testing predetermined hypotheses. . Included in quantitative methods are experimental and survey methods, therefore the method used in this research is a survey method to obtain data from certain natural (not artificial) places, but researchers carry out treatments in collecting data, for example by distributing questionnaires, tests , structured interviews and so on. Based on the results of the research above with 40 respondent answers and 30 indicators or statements, the researcher obtained results using several tests including a validity test to correct and find out whether from each statement in the questionnaire the number of each variable from the test results was known, that the calculation results are valid. Then the researcher continued with the reliability test, t test (partial), f test (simultaneous), knowing that the independent variables together had a significant effect on the dependent variable, thus from these two data tests the hypothesis was accepted. This means that the Ambon Tribune Online Media has an influence on fast information to the public. Next, the researcher used a simple regression test and coefficient of determination test to calculate the magnitude of the influence of the independent variable on the dependent variable, so it can be shown that the percentage influence of the Ambon Tribune Online Media is 49.6%, while the remaining 50.4% is influenced by other indicators. Variable Y is fast information to the public with indicators namely; Maluku information can, health information, local eye information choose to have a significant effect on variable X so that the hypothesis results are accepted.